Bond strength and bond stress-slip response in reinforced concrete - Rao, G. Appa; Sultana, Faiz; Pandurangan, K. (Journal of Structural Engineering, 2025)
Some experimental investigations on the bond strength and analytical modeling of bond stress-slip response in reinforced concrete (RC) have been reported. The effect of strength of concrete, bar diameter, embedment length and type of confinement has been studied. Tests were conducted on pull-out specimens. The parameters of the study include; two embedment lengths (50 mm and 150 mm), two bar diameters (16 mm and 20 mm) and two concretes (40 MPa and 50 MPa). The effect of confinement was also studied by providing different types of confinement such as lateral ties and spirals along with control specimens without confinement. The test results show that the bond strength decreases as the length of embedment increases. The effect of bar diameter is negligible in the range of diameters adopted. As the compressive strength of concrete increases, the bond strength increases and the slip at failure decreases. The bond strength increases with lateral confinement in general. The failure in concrete with spiral reinforcement was relatively ductile. The measured bond strength of concrete ranges between 9.0 MPa and 19.0 MPa in confined concrete. In unconfined concrete, it ranges between 60 to 70% of the confined strength. Splitting failure of concrete was predominant in unconfined concrete, which was altered to pullout type by providing with lateral confinement. The bond stress-slip responses have been idealized in concrete with and without confinement. The bond stress-slip response in the post-peak region has been observed to be relatively steep as the strength of concrete increases.